Inhibition of cyclooxygenase-1 does not reduce mortality in post-ischemic stroke rats. (15th October 2020) - Rostevanov, Ira S.; Boyko, Matthew; Ferorelli, Savina; Scilimati, Antonio; Perrone, Maria Grazia; Kaplanski, Jacob; Zlotnik, Alexander; Azab, Abed N.
Highlights: Inflammation contributes to the pathophysiology of several neurological disorders, including ischemic stroke. Post-ischemic brain is characterized by a prominent inflammatory response. The involvement of cyclooxygenase (COX)-1 enzyme in post-ischemic stroke inflammation is not fully understood. A highly selective inhibitor of COX-1 – mofezolac – did not significantly alter neurologic deficits and mortality in post-stroke rat. Mofezolac significantly attenuated post-stroke fever. Abstract: Background: Ischemic stroke is one of the leading causes of mortality and morbidity. The currently available non-invasive therapeutic options are not sufficiently efficacious. Post-ischemic brain is characterized by a prominent inflammatory response. Little is known about the involvement of cyclooxygenase (COX)-1 in the pathophysiology of ischemic stroke. Objective: This study was undertaken to examine the effects of a highly selective COX-1 inhibitor – mofezolac – on clinical outcomes and brain inflammatory markers in post-stroke rats. Methods: Stroke was induced by subjecting rats to permanent middle cerebral artery occlusion (MCAO). Control rats underwent a sham surgery. Rats were treated with mofezolac (50 mg/kg, intraperitoneally [ ip ]) once daily for 14 days. Control animals were treated with vehicle. Body temperature (BT), neurological score (NS) and cumulative mortality were monitored at different time points. At the end of the experiment, rats were euthanized and three brain regions (hypothalamus, hippocampus and frontal cortex) were extracted. Levels of interleukin (IL)-6, prostaglandin (PG)E2 and tumor necrosis factor (TNF)-α in these brain regions were determined by ELISA kits. Results: BT, NS and cumulative mortality were all significantly higher in post-MCAO rats than in sham-operated rats, irrespective of the treatment given. BT, NS and mortality rate did not differ significantly between mofezolac-treated and vehicle-treated sham-operated animals. BT was significantly lower in mofezolac-treated as compared to vehicle-treated post-MCAO rats. Mofezolac did not significantly alter NS in post-MCAO rats at any time-point. Cumulative 14-day mortality was non-significantly higher in mofezolac-treated as compared to vehicle-treated post-MCAO rats (48 % vs . 21 %, respectively; P  =  0.184). Mostly, IL-6 and TNF-α levels did not differ between post-MCAO and sham-operated rats and were not affected by mofezolac treatment. In contrast, mofezolac significantly decreased PGE2 levels in post-MCAO rats' brains. Conclusion: Overall, these results suggest that chronic treatment with the selective COX-1 inhibitor mofezolac did not reduce morbidity or mortality in post-stroke rats.